2018
DOI: 10.1002/jcp.27148
|View full text |Cite
|
Sign up to set email alerts
|

Reversine promotes browning of white adipocytes by suppressing miR‐133a

Abstract: Brown adipocytes are characterized by a high number of uncoupling protein 1 (UCP1)-positive mitochondrial content and increased thermogenic capacity. As UCP1-enriched cells can consume lipids by generating heat, browning of white adipocytes is now highlighted as a promising approach for the prevention of obesity and obesity-associated metabolic diseases. Upon cold exposure or β-adrenergic stimuli, downregulation of microRNA-133 (miR-133) elevates the expression levels of PR domain containing 16 (Prdm16), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…White adipose tissue is an important place for the body to store excess energy, and widely distributed in the subcutaneous layer and viscera of the body. 29 As shown in Fig. S3B, † the epididymal adipose index of mice in MC group was significantly higher than that of the NC group, and it could be decreased by 22.30% after supplementeation with APP.…”
Section: App Improved the Pathological Characteristics Of Epididymal ...mentioning
confidence: 79%
“…White adipose tissue is an important place for the body to store excess energy, and widely distributed in the subcutaneous layer and viscera of the body. 29 As shown in Fig. S3B, † the epididymal adipose index of mice in MC group was significantly higher than that of the NC group, and it could be decreased by 22.30% after supplementeation with APP.…”
Section: App Improved the Pathological Characteristics Of Epididymal ...mentioning
confidence: 79%
“…In addition, miR-4331 and miR-133a-3p jointly target BCL2L1 , a potent inhibitor of cell death promoting cell survival [ 37 ]. Furthermore, miR-133a-3p also promoted apoptosis and inhibited cell proliferation in a variety of cell lines [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that reversine can regulate several biological processes by inhibiting miRNAs. For example, reversine was found to promote browning of white adipocytes by downregulating miR-133a [ 50 ]. The role of reversine in the multipotency acquisition of myoblasts was also achieved through miR-133a silencing [ 51 ].…”
Section: Discussionmentioning
confidence: 99%